Tricyclic sulfones as potent, selective and efficacious RORγt inverse agonists – Exploring C6 and C8 SAR using late-stage functionalization. Issue 23 (1st December 2020) - Shi, Qing; Xiao, Zili; Yang, Michael G.; Marcoux, David; Cherney, Robert J.; Yip, Shiuhang; Li, Peng; Wu, Dauh-Rurng; Weigelt, Carolyn A.; Sack, John; Khan, Javed; Ruzanov, Max; et al.
Graphical abstract: Abstract: In order to rapidly develop C6 and C8 SAR of our reported tricyclic sulfone series of RORγt inverse agonists, a late-stage bromination was employed. Although not regioselective, the bromination protocol allowed us to explore new substitution patterns/vectors that otherwise would have to be incorporated at the very beginning of the synthesis. Based on the SAR obtained from this exercise, compound 15 bearing a C8 fluorine was developed as a very potent and selective RORγt inverse agonist. This analog's in vitro profile, pharmacokinetic (PK) data and efficacy in an IL-23 induced mouse acanthosis model will be discussed.